2022
DOI: 10.29300/ijsse.v4i2.7562
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pembelajaran Berbasis Case Study Pada Mata Kuliah Pendidikan IPS

Abstract: In universities in the social sciences and education clusters, the social studies education course is one of the important compulsory courses to be taught. In the Social Studies Education course, it is hoped that it can contribute to growing student national awareness, social insight, social spirit, and social sensitivity so as to foster good social interaction in social life. In the learning process, social studies education must prioritize active learning. The case study learning method can make students bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…However, as it develops, movie screenplays have many writing models. Broadly speaking, there are two models of screenwriting, namely the simple form model and the complex form model (Pernantah, 2019). Based on this explanation, it can be concluded that the definition of a screenplay is a written guideline that describes the course of a movie story.…”
Section: Scenariomentioning
confidence: 99%
“…However, as it develops, movie screenplays have many writing models. Broadly speaking, there are two models of screenwriting, namely the simple form model and the complex form model (Pernantah, 2019). Based on this explanation, it can be concluded that the definition of a screenplay is a written guideline that describes the course of a movie story.…”
Section: Scenariomentioning
confidence: 99%
“…Case study disini dilaksanakan sebagai contoh nyata tentang bagaimana Humas menghadapi masalah di dalam organisasi dan case studi adalah salah satu metode yang bagus dalam menyelidiki akibat dan peningkatan potensial yang muncul dari proses ceramah (Pernantah et al, 2022) . Pada proses seminar yang mana menggunakan metode contoh yang nyata diharapkan dapat memberikan peningkatan kerjasama dan lebih memahaminya peserta akan tugas dan pokok Humas di organisasi.…”
Section: Metodeunclassified
“…Menurut Bonwell dan Eison dalam (Aziz, 2018, p. 152), tersebut meliputi: 1) perubahan dalam populasi dan kepemimpinan yang berdampak pada dinamika ekosistem, 2) fokus pada pengembangan keterampilan berpikir analitis dan kritis daripada penyampaian informasi oleh guru, 3) siswa tidak hanya mendengarkan, tetapi melakukan aktivitas yang terkait dengan materi pelajaran, 4) fokus pada nilai-nilai dan sikap terkait subjek pembelajaran, dan 5) adanya respon yang lebih cepat dalam proses belajar. Karakteristik tersebut juga mendapatkan dukungan dari Asiah yang dikutip dari (Pernantah, 2019) yang menjelaskan pentingnya metode pembelajaran aktif dengan beberapa alasan. Alasan tersebut termasuk: 1) pengaruh signifikan terhadap proses belajar siswa, 2) efektivitas metode interaktif dalam meningkatkan kemampuan berpikir siswa, 3) keterlibatan siswa dalam tugas-tugas berpikir tingkat lanjut, dan 4) kemampuan memenuhi berbagai preferensi belajar siswa.…”
Section: Hasil Dan Pembahasan Model Pembelajaran Active Learningunclassified